Determination of Total Flavonoid Content, Antioxidant and Antibacterial Activities of Yellow Root (Fibraurea tinctoria L.) - Yansyah, Rudi (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2025)
Abstract. Yellow root (F. tinctoria) is one of endemic plants from Kalimantan and commonly used by local society as a traditional medicine. Alkaloids are the main chemical constituent and has been reported widely. Unfortunately, other secondary metabolites such as flavonoids and terpenoids are scarce. Total flavonoid contents was determined by a spectrophotometric method, DPPH method was conducted for antioxidant activity, and antibacterial activity against Staphylococcus aureus and Escherichia coli was measured by the well diffusion method. The result showed that methanol fraction has the highest total flavonoid content with 52.23 ± 0.00781 mg QE/g extract. Methanol extract, fractions of methanol and ethyl acetate exhibited weak antioxidant activity with IC50 values of 472.5; 390.6; and 369.3 mg/L, respectively. The antibacterial activity of the three samples against Staphylococcus aureus at a concentration of 50 µg/µL showed a weak-medium category.